2006
DOI: 10.1111/j.1744-313x.2006.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HLA‐DQB1 gene polymorphisms in asymptomatic HBV carriers and chronic hepatitis B patients in the Chinese Han population

Abstract: Host genetic factors and environment factors including hepatitis B virus (HBV) genotype are widely viewed as common basis of the different outcomes of HBV infection. Human leucocyte antigen (HLA) plays an important role in immunological reaction to HBV infection. The study aimed to explore whether the HLA-DQB1 allele polymorphisms are associated with the outcomes of HBV infection in the Chinese Han population. One hundred and thirty-four asymptomatic HBV carriers and 139 chronic hepatitis B patients were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Hence, to overcome this error, the P value was corrected by Bonferroni inequality method21. In various other studies, DQA1*0102, DQA1*03012627 and DQB1*0302, DQB1*0609, DQB1*0503, DQB1*03031228 alleles have been reported to be showing protective effect from developing chronic HBV infection.…”
Section: Discussionmentioning
confidence: 87%
“…Hence, to overcome this error, the P value was corrected by Bonferroni inequality method21. In various other studies, DQA1*0102, DQA1*03012627 and DQB1*0302, DQB1*0609, DQB1*0503, DQB1*03031228 alleles have been reported to be showing protective effect from developing chronic HBV infection.…”
Section: Discussionmentioning
confidence: 87%
“…However, these associations were no longer significant after Bonferroni correction. In other studies, HLA‐DQA1*0301,*0302, *0501 and DQB1*0301, *0303, *0503 had also been reported to have associations with chronic HBV infection (Thio et al ., 1999; Jiang et al ., 2003; Lu et al ., 2006; Xi‐Lin et al , 2006). However, in our study, we did not ascertain these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the up-regulation of ZNRD1 may inhibit DNA damage and enhance DNA repair capacity, which has been identified as a novel negative modifier in carcinogenesis [11, 12]. As we all kown, genes in the HLA region on chromosome 6 (such as HLA-DP and HLA-DQ , which were expressed as surface antigens and determine the immune response to virus infection) were associated with HBV infection and progression [25]. Which is more evidence that ZNRD1 and HLA play alike roles in cancer risk and virus infection.…”
Section: Discussionmentioning
confidence: 99%